Marking the counterfactual: ERP evidence for pragmatic processing of German subjunctives - Kulakova, Eugenia; Freunberger, Dominik; Roehm, Dietmar (Frontiers in Human Neuroscience, 2014)
Counterfactual conditionals are frequently used in language to express potentially valid reasoning from factually false suppositions. Counterfactuals provide two pieces of information: their literal meaning expresses a suppositional dependency between an antecedent (If the dice had been rigged ...) and a consequent (… then the game would have been unfair). Their second, backgrounded meaning refers to the opposite state of affairs and suggests that, in fact, the dice were not rigged and the game was fair. Counterfactual antecedents are particularly intriguing because they set up a counterfactual world which is known to be false, but which is nevertheless kept to when evaluating the conditional’s consequent. In the last years several event-related potential (ERP) studies have targeted the processing of counterfactual consequents, yet counterfactual antecedents have remained unstudied. We present an EEG/ERP investigation which employed German conditionals to compare subjunctive mood (which marks counterfactuality) with indicative mood at the critical point of mood disambiguation via auxiliary introduction in the conditional’s antecedent. Conditional sentences were presented visually one word at a time. Participants completed an acceptability judgement and probe detection task which was not related to the critical manipulation of linguistic mood. ERPs at the point of mood disambiguation in the antecedent were compared between indicative and subjunctive. Our main finding is a transient negative deflection in frontal regions for subjunctive compared to indicative mood in a time-window of 450-600 ms. We discuss this novel finding in respect to working memory requirements for rule application and increased referential processing demands for the representation of counterfactuals’ dual meaning. Our result suggests that the counterfactually implied dual meaning is processed without any delay at the earliest point where counterfactuality is marked by subjunctive mood.